Weak isotopic fractionation of dissolved O2 during community respiration. Issue 8 (21st June 2022) - Wurgaft, Eyal; Musan, Israela; Rivlin, Tanya; Luz, Boaz
Abstract: The isotopic composition of dissolved O2 (δ 18 O) in aquatic environments is strongly affected by the preferential uptake of the lighter isotopologue during biological consumption processes. Numerous studies have shown that during incubation experiments, the isotopic effect of microorganism respiration ( ε organism ) is on the order of −20‰. However, studies of the co‐variations of O2 and δ 18 O in natural environments show considerably weaker in situ fractionation ( ε app ). A possible explanation for this discrepancy is that a significant fraction of the O2 consumption is diffusion‐limited. Although this is a generally accepted mechanism in sediments, it cannot explain the weak fractionations observed in mid‐ocean sites. Here, we analyze a time series of O2, δ 18 O, and auxiliary data from the northern Gulf of Aqaba (Red Sea). Although an incubation experiment showed strong fractionation against the heavy isotopologue ( ε organism = −24.5‰), the in situ ε app was only −14‰ in deep water isolated from the photic zone. We show that this result requires an additional O2 consumption mechanism with weak fractionation, rather than mixing, and suggest that this mechanism is diffusion‐limited respiration into aggregates of organic material. We estimate that this mechanism could be responsible for 30% of the O2 consumption in the Gulf and suggest that it may also constitute a major O2 consumption pathway in the world's oceans.